If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(2.5x)=4x+3
We move all terms to the left:
2(2.5x)-(4x+3)=0
We add all the numbers together, and all the variables
2(+2.5x)-(4x+3)=0
We multiply parentheses
4x-(4x+3)=0
We get rid of parentheses
4x-4x-3=0
We add all the numbers together, and all the variables
-3!=0
There is no solution for this equation
| 4=32/c | | y+2.85=7.93 | | 50+3x=107 | | 2n+2=48 | | 8=8-3x20 | | w+4/7=12/w-1 | | 10=3−–k | | -1265=11(11x-38) | | 48-15x=-51-18x | | -x-1=4x+39 | | 15x3=15 | | 5x+1/2x=22+7/2x | | 2x^2+15=8x-5 | | 11/12=3/4a | | 6s^2s=7 | | 12(x-3=108 | | 15x3=45 | | m=7=12 | | 1-9=13-10p | | 0.5(2x-10)=9 | | 8+m=27* | | 9m+6^2=15^2 | | 1-9p=-10p | | 1/z-2=5/2z-1/2 | | -2(a+3)=-18 | | -2(n-12)+1=-2n+5 | | x/47=53 | | 6t-t=25 | | -18=n=2 | | 4.5g+4=1.5g+13 | | m-15-15=9-15 | | 5x+2=2x+14 |